2003
DOI: 10.1271/bbb.67.1451
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity Effect ofDioscorea nipponicaMakino with Lipase-inhibitory Activity in Rodents

Abstract: In the process of screening for pancreatic lipase inhibitors, which could be used as an anti-obesity measure, the methanol extract of Dioscorea nipponica Makino powder (DP) appeared to have potent inhibitory activity against porcine pancreatic lipase with an IC50 value of 5-10 microg/ml, where the enzyme activity was assayed by using 4-methylumbelliferyl oleate as a substrate. Further purification of active components present in the herb generated dioscin that belongs to the saponin family. Dioscin and its agl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(107 citation statements)
references
References 10 publications
(11 reference statements)
3
99
0
5
Order By: Relevance
“…9) Biological activities of Dioscorea species against diverse metabolic disorders including diabetes and obesity have been already documented. 10,11) However, anti-obesity effect of certain extract derived from D. oppositifolia in animal model remains to be defined. Here, based on the previous in vitro results of D. oppositifolia, we investigated the direct effect of D. oppositifolia n-BuOH extract on obesity induced by highfat diet in animal model.…”
mentioning
confidence: 99%
“…9) Biological activities of Dioscorea species against diverse metabolic disorders including diabetes and obesity have been already documented. 10,11) However, anti-obesity effect of certain extract derived from D. oppositifolia in animal model remains to be defined. Here, based on the previous in vitro results of D. oppositifolia, we investigated the direct effect of D. oppositifolia n-BuOH extract on obesity induced by highfat diet in animal model.…”
mentioning
confidence: 99%
“…However, the restraining effects and involved mechanisms of DNE on cancer metastasis have not yet to be elucidated. DNE has reported antiobesity and antiinflammation effects in both in vivo and in vitro experimental models (Kwon et al 2003;Xiao et al 2010). To date, no studies describe the anticancer effects of DNE on neuroblastoma cancer Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…The rhizome of Dioscorea nipponica Makino has high saponin content and use in folk medicine as treatment for coronary heart disease, asthma, rheumatoid arthritis, and hyperlipidemia, as well as a source of hormonal sterol synthesis precursors (Yoshikawa et al 2007). Recently, studies revealed that Dioscorea plant extracts exert antiobesity effects (Kwon et al 2003;Xiao et al 2010). However, limited studies exist concerning the anticancer effects of D. nipponica.…”
Section: Introductionmentioning
confidence: 99%
“…상엽 (桑葉, Folium Mori)에 대한 연구로는 혈당강하 효과 14,15) 와 cholesterol 감소 및 동맥경화증, 고지혈증, 당뇨병 예방치료 효과 16) 가 있고, 산약 (山藥, Rhizoma Dioscoreae)에 대한 연구로는 항산화 작용 17,18) , 고혈당 19) 과 비만 20) 을 억제하는 작용과 지질대사 개선 Cells were incubated with MLHM at the indicated concentration (0.04-4mg/mL) for 24h and the growth rate was assessed by MTT assay. 1: control; 2: MLHM 0.04mg/ml; 3: MLHM 0.4mg/ml; 4: MLHM 4mg/ml All values are mean ± SD.…”
Section: Herb Nameunclassified